1977
DOI: 10.1093/oxfordjournals.aje.a112424
|View full text |Cite
|
Sign up to set email alerts
|

The Reporting of Communicable Diseases

Abstract: Surveillance of communicable diseases in the United States depends on the reporting of cases by primary physicians. It is widely recognized, however, that significant numbers of such cases are not reported. Reporting rates for many communicable diseases have never been determined. In this study, discharge records of 11 hospitals in Washington, DC were searched for cases of selected communicable diseases, and the percentage of these cases reported was determined. Five hundred and seventy of 93,563 (0.61%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(39 citation statements)
references
References 0 publications
0
35
0
4
Order By: Relevance
“…Much of the surveillance for infectious diseases has been passive surveillance, and therefore often incomplete. 24,25 More recent surveillance efforts, particularly for TB and HIV or AIDS, have been active, and have demonstrated improved reporting rates. [26][27][28] While the completeness of reporting for TB in adults has been explored, 22,[29][30][31][32][33] this study is the first assessment of completeness of reporting performed exclusively for a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the surveillance for infectious diseases has been passive surveillance, and therefore often incomplete. 24,25 More recent surveillance efforts, particularly for TB and HIV or AIDS, have been active, and have demonstrated improved reporting rates. [26][27][28] While the completeness of reporting for TB in adults has been explored, 22,[29][30][31][32][33] this study is the first assessment of completeness of reporting performed exclusively for a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Under-ascertainment is a problem common to all passive surveillance systems, including those that monitor the occurrence of life-threatening infectious diseases. 23,24 The perceived importance of an illness and the clinical outcome associated with a particular episode (e.g., recovery versus death) may influence the rate of reporting; however, estimates for completeness of reporting of deaths attributable to other nationally notifiable diseases reveal similarly low percentages, including 33% for pertussis and 40% for tetanus. 10,11 Application of capture-recapture methods require several assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that only a fraction of communicable disease cases are reported by the notifiable diseases reporting system [4]. The new surveillance system revealed that, for example, in 1984 only 33% of cases of gonorrhoea notified through the sentinel laboratories [5] and 31 % of cases of malaria [6] were reported through the normal channels.…”
Section: Discussionmentioning
confidence: 99%